Interactions Between Pseudomonas Immunotoxins and the Plasma Membrane: Implications for CAT-8015 Immunotoxin Therapy - Bokori-Brown, Monika; Metz, Jeremy; Petrov, Peter G.; Mussai, Francis; De Santo, Carmela; Smart, Neil J.; Saunders, Sarah; Knight, Bridget; Pastan, Ira; Titball, Richard W.; Winlove, C. Peter (Frontiers in Oncology, 2018)
Acute Lymphoblastic Leukaemia (ALL) remains the most frequent cause of cancer-related mortality in children and novel therapies are needed for the treatment of relapsed/refractory childhood ALL. One approach is the targeting of ALL blasts with the Pseudomonas immunotoxin CAT-8015. Although CAT-8015 has potent anti-leukaemia activity, with a 32 % objective response rate in a phase 1 study of childhood ALL, haemolytic-uremic syndrome (HUS) and vascular leak syndrome (VLS), major dose-limiting toxicities, have limited the use of this therapeutic approach in children. Investigations into the pathogenesis of CAT-8015-induced HUS/VLS are hindered by the lack of an adequate model system that replicates clinical manifestations, but damage to vascular endothelial cells (ECs) and blood cells are believed to be major initiating factors in both syndromes. Since there is little evidence that murine models replicate human HUS/VLS, and CAT-8015-induced HUS/VLS predominantly affects children, we developed human models and used novel methodologies to investigate CAT-8015 interactions with red blood cells (RBCs) from paediatric ALL patients and ECs of excised human mesenteric arteries. We provide evidence that CAT-8015 directly interacts with RBCs, mediated by Pseudomonas toxin. We also show correlation between the electrical properties of the RBC membrane and RBC susceptibility to CAT-8015-induced lysis, which may have clinical implication. Finally, we provide evidence that CAT-8015 is directly cytototoxic to ECs of excised human mesenteric arteries. In conclusion, the human models we developed constitutes the first, and very important, step in understanding the origins of HUS/VLS in immunotoxin therapy and will allow further investigations of HUS/VLS pathogenesis.